2014
DOI: 10.1111/epi.12651
|View full text |Cite
|
Sign up to set email alerts
|

Are afebrile seizures associated with minor infections a single seizure category? A hospital‐based prospective cohort study on outcomes of first afebrile seizure in early childhood

Abstract: SUMMARYObjective: To explore if afebrile seizures associated with minor infections are a single category of seizure, or a set of different kinds of seizures. Methods: We conducted this prospective cohort study on three kinds of first afebrile seizure: first afebrile seizure associated with gastrointestinal infection (AS-GI), first afebrile seizure associated with nongastrointestinal infection (AS-nGI), and first unprovoked seizure (US). The Kaplan-Meier estimate risks of recurrent seizures were analyzed and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…Rotavirus is the most common agent associated with CwG. The rotavirus antigen was found in the stool of 22.35% of our patients at the time of initial CwG diagnosis, which is similar to rates in previous reports [3,4,15]. Direct CNS viral invasion and viral enterotoxin NSP4-induced disruption of calcium homeostasis have been hypothesized as possibly underlying the genesis of seizures in CwG [12].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Rotavirus is the most common agent associated with CwG. The rotavirus antigen was found in the stool of 22.35% of our patients at the time of initial CwG diagnosis, which is similar to rates in previous reports [3,4,15]. Direct CNS viral invasion and viral enterotoxin NSP4-induced disruption of calcium homeostasis have been hypothesized as possibly underlying the genesis of seizures in CwG [12].…”
Section: Discussionsupporting
confidence: 88%
“…Zhang et al found that CwG versus AS-nGI and US at onset are two distinguishable kinds, with the latter twos sharing the similar relapse rates. Afebrile seizures recurred in 100% and 92.9% cases diagnosed with AS-nGI and US, respectively [15]. In contrast, in the present study, no cases with two or more episodes of afebrile seizures were found in the AS-nGI group during over 3 years of follow-up, while one of the three patients in the US group presented with US recurrence.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations